PENERAPAN PENDIDIKAN KARAKTER PEMBELAJARAN IPS DI SEKOLAH DASAR - Puji Hartono, Deni (JIPD (Jurnal Inovasi Pendidikan Dasar), 2024)
Abstract: Character education is a system that teaches students character values ​​so that they can be applied in life in the family, school, community and country, and are able to make positive contributions to the people around them. Students are taught to become complete human beings with character in the dimensions of mind, soul, body, emotions and will. Character education is all efforts made by teachers to influence student character. Teachers help students develop their character. For example, how the teacher behaves, how the teacher speaks and delivers material, as well as the teacher's tolerance, and various other related things.